Microbial keratitis in Southern Malawi: a microbiological pilot study - Timothy Neal; Dean Everett; Stephen B Kaye; Alistair Darby; Moira Gandiwa; Shaffi Mdala; Caroline E Corless; Rose Herbert; Nicholas A V Beare; Tobi F Somerville; Thokozani Zungu; Malcolm J Horsburgh; et al. (BMJ Open Ophthalmology)
Objective Microbial keratitis (MK) is a significant cause of blindness in sub-Saharan Africa. We investigated the feasibility of using a novel corneal impression membrane (CIM) for obtaining and processing samples by culture, PCR and whole-genome sequencing (WGS) in patients presenting with suspected MK in Malawi.Methods and analysis Samples were collected from patients presenting with suspected MK using a 12 mm diameter polytetrafluoroethylene CIM disc. Samples were processed using culture and PCR for Acanthamoeba, herpes simplex virus type 1 (HSV-1) and the bacterial 16S rRNA gene. Minimum inhibitory concentrations of isolates to eight antimicrobials were measured using susceptibility strips. WGS was used to characterise Staphylococcus aureus isolates.Results 71 eyes of 71 patients were included. The overall CIM isolation rate was 81.7% (58 positive samples from 71 participants). 69 (81.2%) of isolates were Gram-positive cocci. Coagulase-negative Staphylococcus 31.8% and Streptococcus species 14.1% were the most isolated bacteria. Seven (9.9%) participants were positive for HSV-1. Fungi and Acanthamoeba were not detected. Moxifloxacin and chloramphenicol offered the best coverage for both Gram-positive and Gram-negative isolates when susceptibility was determined using known antimicrobial first quartile concentrations and European Committee on Antimicrobial Susceptibility Testing breakpoints, respectively. WGS identified known virulence genes associated with S. aureus keratitis.Conclusions In a resource-poor setting, a CIM can be used to safely sample the cornea in patients presenting with suspected MK, enabling identification of causative microorganisms by culture and PCR. Although the microbiological spectrum found was limited to the dry season, these preliminary results could be used to guide empirical treatment.